Comparison between Spinal Vs General Anesthesia in Patients Undergoing Vaginal Hysterectomy Outcome and Prognosis - Chaudhry , Ammad Hasan; Riaz , Iqra; Shehzad, Farrukh; Sarwar, Mariam; Shabnam; Wahid, Faisal (Indus Journal of Bioscience Research, 2025)
Introduction: The selection of anesthesia defines how patients perform after vaginal hysterectomy. When used for vaginal hysterectomy spinal anesthesia delivers better pain control following surgery together with decreased blood loss during the procedure yet it can produce adverse effects which include post-Dural puncture headache (PDPH) and urinary retention. Objective: The research compared vaginal hysterectomy performance between spinal and general anesthesia by evaluating blood loss amounts during surgery as well as postoperative pain levels and opioid requirements and hospital duration and anesthesia side effects. Methodology: The evaluation of women who underwent vaginal hysterectomy took place during a one-year period from April 2023 to March 2024, at Combined Military Hospital (CMH), Peshawar with 118 patients enrolled. The anesthetic selection of the patients was conducted based on clinical requirements between spinal or general anesthesia. The study collected key measurement data points on blood loss together with pain scores and opioid use and hospital length of stay and complications. The results were analyzed through the Chi-square test together with independent t-test and Mann-Whitney U test where p less than 0.05 defined statistical significance. Results: The patients receiving SA experienced decreased blood loss (185.6 ± 45.3 mL vs. 247.8 ± 61.4 mL, p < 0.001) and reported decreased pain together with reduced hospital stays (28.4 ± 6.2 hours vs. 35.1 ± 7.4 hours, p < 0.001) in comparison to the general anesthetic group. The frequency of urinary retention amounted to 12.5% within the SA group alongside 5.1% incidence of PDPH whereas GA led to elevated postoperative nausea and vomiting frequencies (38.9% vs. 16.9%, p = 0.004). Conclusion: Vaginal hysterectomy results in superior outcomes when spinal anesthesia is used since it causes decreased blood loss along with reduced pain while shortening hospital stay periods. The nurse should implement proper management strategies for all complications connected to the procedure.